Toxic maculopathy - Markovska V.; Buzarovska K. (My University, 2015)
Purpose: To describe clinical, angiographic and optical tomography feathers of tamoxifen, niacin and chloroquine maculopathy and to analyze the bibliography review of previous studies. Methods: A review of history, clinical examination and findings of FFA and OCT was conducted.Results:3 patients with niacin induced cystoid maculopathy without leakage on FFA , 3 patients with tamoxifen maculopathy, 1 with cellophane maculopathy with or without of cystoid macular edema, 1 case of tamoxifen maculopathy in the eyes with sarcoidosis and 2 cases of hydrochlorquine sulfat maculopathy used for the treatment of autoimmune conditions. Conclusion: Patients receiving tamoxifen should be monitored with OCT for funduscopicaly invisible changes in the inner retinal layers once a year. All patients using antimalaric drugs should be followed and documented since the beginning of the therapy until they reach the cumulative dose and after it. The patients using high dose of oral niacin, has to be examined and evaluated only if they complain for visual impairment.